Confirming Tonality at Residences Influenced by Wind Turbines - K.G. Palmer William (Journal of Energy Conservation, 2020)
For 5 years, since the start-up of an array of 140 wind turbines, residents have filed complaints with the Ontario Ministry of the Environment (the regulator), and K2 Wind (the operator). Residents complained that the turbines produce a tonal sound, and that the irritation this produced impacted their sleep, their health, and the enjoyment of their property. To confirm tonality from the wind turbines, this research examined over 200 data examples from two families. These families collected data by two independent methods, a continuously recording system, and by making selected audio recordings. The recorded data was correlated with the wind turbine operational performance, and local weather conditions. The correlated data was analyzed for tonality using international standard evaluation methods. The analysis confirmed over 84% correlation between complaints of irritating conditions, and tonality from 5 dB to over 20 dB. Finally, the results showed that the assumption of the regulator to only require assessment of compliance when the resident was downwind of the nearest wind turbine was incorrect. Most complaints arose from other wind directions. Neither was the regulator’s assumption correct that curtailing the wind turbine operation to continue operating at only partially reduced outputs would give remediation. The research concludes that tonality arises consistent with the wind turbine operation, identifying a critical need to revise the practices to prevent chronic irritation. In the original issuance of this paper, the author inadvertently erred by stating that there was a difference between the method for assessing wind turbine tonality of an expert group panel and the method now prescribed by regulations. That statement was incorrect, and the author apologizes for the error and for any confusion it may have caused. The error, miscalculations resulting from the error, where necessary conclusions drawn from erroneous calculations are corrected.
Keywords: wind turbine